Isolation and Screening of Phb Producing Halotolerant Bacterial Strains from A Saline Environment - Nabila, Fathima S; VeenaGayathri, Krishnaswamy (Journal of Biotechnology and Biomedical Science, 2017)
Plastic materials have been used as packaging materials and also have other numerous applications because of their durability and stability. Plastic products are non degradable and they continue to exist in the environment thereby causing a serious threat to the ecosystem. Bioplastics which are biodegradable plastics are emerging out as a boon to overcome the problem of plastic accumulation. Polyhydroxybutyrate or PHB is a bioplastic that serves as an alternative to synthetic plastics. PHB is a lipid reserve material that gets accumulated within the cell wall of micro organisms under stress conditions. Halophilic microorganisms can be of much use in the production of PHB as it is cost – effective and recovery of PHB is much easier in halotolerant organisms. Hence this study focuses on the isolation of PHB producing halotolerant bacterial organisms from marine sources. Screening of PHB positive isolates was done by Sudan Black B and Nile blue A staining. Large scale production of PHB by the efficient bacterial strain was done by using wastewater as the substrate.
Keywords: Polyhydroxybutyrate; Halotolerant; bacterial strains; 16s rRNA sequencing; wastewater